Genetic factors and variability in blood pressure. A brief literature review. - Rogério Fermino; André Seabra; Rui Garganta; José António Ribeiro Maia (Universidade Federal de Santa Catarina, 2009)
The main purpose of this review was to gather relevant information regarding the importance of genetic factors for the variability of blood pressure levels. A search was performed in the Pubmed database, and the following studies were selected: (1) studies reporting familial aggregation with heritability estimates, (2) linkage studies reporting only significant results, and (3) association studies between blood pressure, candidate genes and their allelic variants using a case-control design. Heritability estimates for systolic and diastolic blood pressure ranged from 14 to 68% and from 6 to 62%, respectively. We found significant linkage results for systolic blood pressure on chromosomes 2, 5, 6, 15 and 17. Relevant candidate genes presented disparate results in terms of their association with arterial hypertension. Blood pressure is a polygenic phenotype whose variation is partially mediated by genetic factors. The candidate genes identified do not sufficiently explain arterial hypertension.